Filtered and Unfiltered Cigarette Effect on White Rats Male Reproduction (Rattus norvegicus L.) - Budiantoro, Agung; Farhanah, Nurul Amalia (Jurnal ILMU DASAR, 2024)
Cigarette smoke can cause various health problems, one of which is a decrease in fertility in males. The purpose of this study was to determine the effect of smoke exposure between with and without filter hand-rolled kretek cigarettes (SKT) and white cigarettes on white rats male reproduction: sperm quality in the form of sperm motility and viability, also the structure of seminiferous tubules. This study used 5 treatment groups (KP), namely controls not given exposure to cigarette smoke (KP0), exposure to unfiltered kretek cigarette smoke (KP1), exposure to filtered kretek cigarettes (KP2), exposure to unfiltered white cigarette smoke (KP3) and exposure to secondhand smoke. filtered white cigarettes (KP4) with treatment placement arrangement in a Completely Randomized Design (CRD) and if there is a significant difference, a Duncan Multiple Range Test (DMRT) is carried out. The results obtained on sperm quality, namely sperm motility and viability, decreased. Good quality at KP0 then the quality decreases successively starting from KP1, KP2, KP3 and KP4. The results on histpathological observations of the seminiferous tubules, there were no pathological changes found in all treatments. In contrast to the histopathology of seminiferous tubules, the number of spermatogenic cells showed a significant difference between treatments with the least average spermatogenic count and a decrease in the number of cells from spermatogonia cells to spermatid cells, namely in the treatment group exposure to filtered white cigarette smoke (KP4). Overall, the exposure that caused the most severe impact on all measured parameters was in the treatment group of filtered white cigarette smoke (KP4).